Analysis of the Need for Futuristic Technological Innovation in English-Based Civics Learning in the Society 5.0 Era at MAS Darul Amin Palangka Raya - Irvan Mahendra; Malik Ramadhan Nasution; Bobbitya Putra W; Putri Azzahra Cinta Wahyuni (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Background: The Society 5.0 era demands fundamental transformation in educational paradigms through integration of cyberphysical systems, artificial intelligence, and big data analytics. Pancasila and Citizenship Education (PPKn) faces challenges in integrating national values with global citizenship demands, requiring English-based instruction and futuristic technological support. MAS Darul Amin Palangka Raya encounters strategic challenges in implementing English-based PPKn learning while harmonizing Islamic-Indonesian values with international standards. Aim: This research aims to map readiness levels and analyze factors influencing English-based PPKn learning implementation supported by futuristic technology in the Society 5.0 era at MAS Darul Amin Palangka Raya. Method: This study employed mixed-methods with sequential explanatory design. The quantitative phase utilized Technology Readiness for Futuristic Learning (TRFL) questionnaire adapted from Technology Readiness Index 2.0, involving 201 respondents through proportional stratified random sampling. The qualitative phase conducted semi-structured interviews and focus group discussions with 12 purposively selected informants. Data were analyzed using descriptive statistics, Mann-Whitney U Test, and thematic analysis following Miles, Huberman, and Saldana framework. Results and Dıscussion: Findings revealed aggregate Technology Readiness Index (TRI) score of 2.74 (moderate category), with high optimism (3.42) balanced by security concerns (3.07) and implementation discomfort (2.89). Significant disparities existed between groups, with Grade 10 students showing highest readiness (2.89) while teachers scored lowest (2.45). Qualitative exploration identified six themes: technology perceptions, infrastructure capacity, cultural resistance, learning expectations, security concerns, and implementation preferences. Integration analysis confirmed convergence on ambivalent readiness and age-related gaps, revealing divergence between theoretical optimism and practical concerns. Conclusion: MAS Darul Amin Palangka Raya demonstrates conditional readiness requiring phased implementation addressing infrastructure limitations, teacher capacity building, cultural adaptation, and equity considerations for sustainable transformation toward Society 5.0 educational paradigm. Keywords: Society 5.0, Futuristic Technology, English-Based Learning, Civics Education, Technology Readiness